PENGEMBANGAN LKPD BERBASIS CULTURALLY RESPONSIVE TEACHING UNTUK KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMA - Rasylin, Miftah Muthmainna; Muchlish, Effie Efrida; Hanifah, Hanifah (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
In the 21st century, students are expected to have various competencies such as critical thinking and problem-solving skills, creativity, communication skills, and collaboration skills. 21st century education and independent curriculum emphasize the importance of the teacher's role in integrating learning approaches that respect cultural diversity, one of which is Culturally Responsive Teaching (CRT). The purpose of this study was to develop a student worksheet (LKPD) based on Culturally Responsive Teaching (CRT) to improve the creative thinking skills of secondary school students in mathematics. This research was conducted from 14 to 26 October 2024 at SMAN 4 Rejang Lebong involving grade X students. The type of research is Research Development (RD) with the ADDIE development model. The LKPD developed was validated by experts in the field of mathematics. The study findings showed that the LKPD produced met the eligibility criteria very well, with a validation score of 92% for the construction aspect, 92% for the material aspect, and 89% for the language aspect. A limited trial on grade X students showed a positive response of 96%. The level of effectiveness of LKPD in class X.7 with 35 students reached 73%, while class X.8 with 34 students reached 77%, both included in the effective category. Based on the results of the study, it can be concluded that LKPD is valid, practical, and effective, making it suitable for use.